Bibliometric Analysis of The Altman Model - Ancuta A. CHELBA; Veronica GROSU; Mihaela I. SOCOLIUC (Communications of International Proceedings, 2022)
The issue of companies' risk of bankruptcy and the ways in which it is solved occupy a central place in international scientific research, especially in the current pandemic context. The aim of this paper is to adopt a mixed methodology of systematic literature review and bibliometric, network and content analysis based on a number of 502 papers identified on the Web of Science (WoS) and SCOPUS. The purpose of this literature review combined with bibliometric analysis is to provide a research perspective on the directions for improving or simplifying the Altman model adapted to the new global economic conditions, but also to objectively identify the current state of research on to the methods and techniques of assessing the risk of bankruptcy. The results obtained are represented by the construction of a research agenda in which are recorded all the stages registered in the evolution of determining the risk of bankruptcy of companies, simultaneously with the evolution of the global economic context. We believe that the agenda provided can be a potential tool or a starting point for further research studies aimed at adjusting current bankruptcy risk assessment models or determining a bankruptcy assessment model.
Keywords: evaluation of the bankruptcy risk; bankruptcy; Altman model; bibliometric analysis